Rancang Bangun Sistem Pendukung Keputusan Penentuan Lokasi Penyuluhan PHBS Tatanan Rumah Tangga Pada Puskesma Sedati - Ardhy, Nur Sakti Yanuar; Sulistiowati, Sulistiowati; Sutomo, Erwin (Jurnal Sistem Informasi Universitas Dinamika (JSIKA), 2016)
Health Promotion is the form of the Sedati local government clinic effort to aid people in the scope of region be able to healthy live. One of the important program owned Sedati Health Promotion is providing information and counseling about the clean and healthy behavior. But, The problems that looks and being faced by promkes this time regarding the determination of the location of clean and healthy behavior counseling. The process of determining which do at this time only consider economical side, that mean which the nearest location that becomes the main priority to give counseling. Its ineffective way, because of health problem is settled quickly Not be seen from a distance or close to her location. In addition a delay in the process of determining often occur so that impacted on the implementation of counseling activities.The problem can be resolve with the Decision Support System which can determination of the decision process of determining the right location of counseling with a exact method of calculation. The method that can support the decision is Analytical Hierarchy Process (AHP), because the result of decision was in the form of the value of priority.Based on the implementation and evaluation has been done, the system can assist the Health Promotion to determine the location of clean and healthy behavior counseling in the form of value of priority effectively and efficiently. So, that the implementation of counseling can be started immediately